Homing pigeon navigational ontogeny: no evidence that exposure to a novel release site is sufficient for learning - Morford, J; Gagliardo, A; Guilford, T (Elsevier, 2024)
The navigational mechanisms of homing pigeons, Columba livia, have been extensively studied and represent a useful model for the navigation of birds and other animals. Pigeons navigate with an olfactory map and sun compass from unfamiliar areas and, in familiar areas, are largely guided by visual landscape cues, following stereotyped and idiosyncratic routes. However, the mechanisms by which they gain familiarity, improve their navigation and transition between navigational strategies during learning are not fully understood. Addressing these outstanding questions in this navigational model will help to improve our understanding of navigational ontogeny. We sought to investigate whether passive exposure to the cues at a site, without release, was sufficient for navigational learning, given that pigeons can determine the home direction before taking off. We exposed pigeons to cues at a novel site before returning them to the site the next day and releasing them alongside controls. We found no differences in the directional distributions, mean vector lengths, virtual vanishing times, efficiency indices or homing efficiency indices between birds that had and had not previously visited the site. We therefore found no evidence to suggest that passive exposure to the cues at a novel site was sufficient to facilitate a detectable improvement in navigational performance. There are three possible explanations for this result: first, a larger sample size would have detected a weak effect of learning; second, passive exposure to a release site is insufficient to generate navigational learning; and third, pigeons learn from passive exposure but do not rely upon this information, showing no difference in performance, despite learning. We discuss these three explanations with reference to previous findings on navigational learning in homing pigeons. We suggest that experiments should continue to examine navigational ontogeny in homing pigeons to help address this major problem for the field of navigation.